The Influence of Cultivation System on Distribution Profile Of 137cs and Erosion / Deposition Rate - Suhartini, Nita (Universitas Muhammadiyah Surakarta, 2007)
137Cs radiogenic content in the soil can be used to estimate the rate of erosion and deposition in an area occurring since 1950âs, by comparing the content of the 137Cs in observed site with those in a stable reference site. This experiment aimed to investigate the influence of cultivation type on distribution profile of 137Cs and distribution of erosion and deposition rate in cultivated area. A study site was small cultivated area with slope steepness <10o and length 2 km located in Bojong â Ciawi. For this purpose, the top of a slope was chosen for reference site and three plot sites were selected namely Land Use I that using simple cultivation, Land Use II that using simple cultivation with ridge and furrow, and Land Use III using machine cultivation. The results showed that cultivation could make a movement of 137Cs to the deeper layer and ridges and furrows cultivation system could minimized an erosion process. The net erosion and deposition for land Use I, II and III were -25 t/ha/yr , 24 t/ha/yr and -58 t/ha/yr, respectively.